KURIKULUM TERPADU DI ERA GLOBALISASI: STUDI KUALITATIF PENERAPAN KURIKULUM MERDEKA, ISMUBA,UMI, DAN CAMBRIDGE DI SD MUHAMMADIYAH 6 JAKARTA - Erika Ramadhani Salma; Hibatillah Hasanah; Salwa Az Zahrah; Arum Fatayan (STKIP Subang, 2025)
This study aims to analyze the implementation of four integrated curricula—theMerdeka Curriculum, ISMUBA, UMI, and Cambridge—at SD Muhammadiyah 6Jakarta. The research employs a descriptive qualitative approach, with datacollected through observations, in-depth interviews with the school principal, andliterature reviews. The findings reveal that the integration of these curriculasuccessfully creates a holistic education system encompassing academic,spiritual, and global skill development. The Merdeka Curriculum focuses ondifferentiated learning and character building, while ISMUBA and UMI strengthenIslamic values through religious education and Quranic memorization (tahfidz).The Cambridge Curriculum enhances international literacy in English,Mathematics, and Science. Key challenges include time management, teachertraining, and balancing global and local values. However, stakeholdercollaboration and curriculum flexibility enable the school to achieve its objectives.In conclusion, this multi-curriculum model has the potential to serve as an exampleof balanced value-based and competency-driven education in the globalizationera.